Should Trust Be Stressed? General Trust and Proactive Coping as Buffers to Perceived Stress - Carlander, Anders; Johansson, Lars-Olof (Frontiers in Psychology, 2020)
Stress is becoming an increasingly important public health concern. Assuming that individual levels of trust and coping can buffer psychological stress, we explore validated measures of General Trust (GTS), Proactive Coping (PCI), jointly with Personality (HEXACO) and Intolerance of Uncertainty (IUS), as predictors of Perceived Stress (PSS). Data were collected from Qualtrics research panels using quota sampling to obtain two representative American community samples. The assumed alleviating effects of GTS and PCI on PSS remained but were attenuated when modelled jointly with HEXACO, IUS and socio-economic background variables (SES) in hierarchical regressions. In Study 1 (N = 1213), SES explained 19% and HEXACO 29% of the variance in PSS. Introducing IUS and GTS added significant but small portions of explained variance. In Study 2 (N = 1090), after controlling for SES which explained 18% of the variance, IUS explained an additional 18% of the variance in PSS. Adding GTS to the model showed modest contributions whereas PCI added 9% of explained variance in the final hierarchical step. The findings highlight that GTS and PCI remain important variables even after controlling for well-known factors such as personality and ability to tolerate uncertainty. However, given the weak effects of GTS, to consider trust as a remedy for stress may be of limited use in clinical practice since it could potentially be explained largely as a proxy for a beneficial combination of personality, coping and socioeconomic background.